Computational Thinking for Youth and Adults Education: model, principles, activities and lessons learned - Ortiz, Júlia dos Santos Bathke; Pereira, Roberto (Revista Brasileira de Informática na Educação, 2021)
Computational Thinking (CT) is considered one of the most needed abilities of the 21st Century as the usage of digital resources has become more and more frequent. Research on CT teaching has been growing over the last decade and Brazilian initiatives have focused on Elementary and High School students while less privileged audiences, such as non-literate citizens, are rarely addressed. The lack of literacy affects more than communication, but autonomy for economic, cultural and educational development, social interaction, and also the experience with information and communication technology. Non-literate citizens represent more than 11 million people in Brazil, and Youth and Adults Education (YAE) is an educational modality offered to these citizens. In this article, we present the main results from a Master's research that investigated CT as a means to reduce YAE's students' rejection and fear of technology, aware of their characteristics, contexts, and particularities. In our research, we consider that through the practice of CT people can comprehend how technology works and how it can be used, favoring familiarity, and reducing rejection and fear of technology. Grounded on Computing and Education literature, we conceived a model to plan and conduct initiatives for YAE, applying and studying our model in a case study conducted inside a Brazilian public school during 8 workshops with 17 participants. For the case study, 9 principles to support the practice with YAE students were identified and used to inform 12 activities created/adapted for practicing CT throughout the workshops. A research overview is presented, along with its theoretical grounds to the main results from the case study and lessons learned. Results show the model as promising to inform practices to exercise CT abilities, sensitive to the audience's context.